Has diabetes mellitus glycaemic control improved with introduction of point of care glycated haemoglobin A1c? - Adams, Constance Sandra (My University, 2019)
Background: Diabetes mellitus has long been a cause for local and international concern; in Sub-Saharan Africa the mortality rate from diabetes related complications surpassed that of HIV/AIDS, tuberculosis and malaria combined. Point-of-care (POC) glycated haemoglobin (HbA1c) has been in routine use at a tertiary hospital’s diabetic clinic in Johannesburg, South Africa. The investigator set out to determine if having a readily available result on the day of consultation has had a positive effect on improving glycaemic control. Objectives: The aim of this study was to determine if an immediately available POC HbA1c would result in improved target HbA1c and improved glycaemic control. Methods: 195 Adult attendees of the diabetic clinic who had been attending since before the advent of the POC HbA1c test were recruited. The laboratory HbA1c was compared to the current POC HbA1c to determine if there was any improvement in glycaemic control. Results: The mean HbA1c before the POC test was 8.8% (SD 1.9) and the current POC HbA1c was 8.9% (SD 1.94). There was no statistically significant improvement in glycaemic control. Conclusion: The POC test for HbA1c at a tertiary hospital’s diabetic clinic has not resulted in improved glycaemic control. This important study has shown that the introduction of new technology is not the answer to better diabetic care. Comprehensive diabetic care is multifactorial and relies on intensive efforts of a multidisciplinary team including physician and diabetic nurse educator with active patient participation to ensure optimal glycaemic control.
A research report submitted in partial fulfilment for the degree of Masters in Medicine -Internal Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019
Keywords: Diabetes Merlitus; Endocrine Disease